Effect of kenaf alkalization treatment on morphological and mechanical properties of epoxy/silica/kenaf composite - Jaafar, Che Nor Aiza; Muhammad Rizal, Muhammad Asyraf; Zainol, Ismail (Science Publishing Corporation, 2018)
The mechanical performance of silica modified epoxy at various concentration of sodium hydroxide for surface treatment of multi-axial kenaf has been analyzed. Epoxy resin with amine hardener was modified with silica powder at 20 phr and toughened by treated kenaf fiber that immerses in various concentrations of sodium hydroxide (NaOH) ranging from 0% to 9% of weight. The composite was analyzed through differential scanning calorimetry (DSC) to ensure complete curing process. The mechanical properties of the composites were analyzed through flexural test, Charpy impact test and DSC to ensure the complete curing process. DSC analysis results show epoxy sample was completely cured at above 73°C that verifies the curing temperature for preparation for the composite. Hence, 3% NaOH treated composite exhibits the best mechanical properties, with 10.6 kJ/m2 of impact strength, 54.1 MPa of flexural strength and 3.5 GPa of flexural modulus. It is due to the improvement of fiber-matrix compatibility. Analysis by SEM also revealed that a cleaner surface of kenaf fiber treated at 3% NaOH shown cleaner surface, thus, in turn, improve surface interaction between fiber and matrix of the composite. The composites produced in this work has high potential to be used in automotive and domestics appliances.